Antimicrobial Resistance of Salmonella Strains Isolated from Human, Wild Boar, and Environmental Samples in 2018–2020 in the Northwest of Italy - Valeria Listorti; Aitor Garcia-Vozmediano; Monica Pitti; Cristiana Maurella; Daniela Adriano; Carlo Ercolini; Monica Dellepiane; Lisa Guardone; Elisabetta Razzuoli (Pathogens, 2022)
Antimicrobial resistance is one of the most challenging public health problems worldwide, and integrated surveillance is a key aspect in a One Health control strategy. Additionally, Salmonella is the second most common zoonosis in Europe. We aimed to investigate the circulation of Salmonella strains and their related antimicrobial resistance in human, environmental, and wild boar samples from the northwest of Italy, from 2018 to 2020, to obtain a more comprehensive epidemiological picture. Salmonella Typhimurium 1,4,[5],12:i:-, S. Veneziana and S. Newport were the most common serotypes occurring in humans, the environment, and wild boar, respectively. Antimicrobial resistance was rather common in Salmonella isolates, with those from human displaying the highest degree of resistance against sulfadiazine–sulfamerazine–sulfamethazine (>90% of resistance). Moreover, resistance against azithromycin were exclusively observed in environmental samples, while only 7.7% (95% CI = 1.6–20.8) of wild boar isolates experienced resistance against trimethoprim–sulfamethoxazole. Multidrug resistance concurrently involved up to seven antimicrobial classes in human isolates, including third-generation cephalosporins and fluoroquinolones. Salmonella Typhimurium in humans and serotypes Goldcoast and Rissen from environmental sources showed the highest levels of resistance. This study shows diverse antimicrobial resistance patterns in Salmonella strains isolated from different sources and gives a broad picture of antimicrobial resistance spread in wild animals, humans, and the environment.